A weight management programme for fathers of children aged 4-11 years: cultural adaptation and the Healthy Dads, Healthy Kids UK feasibility RCT - Kate Jolly; Tania Griffin; Manbinder Sidhu; Peymane Adab; Adrienne Burgess; Clare Collins; Amanda Daley; Andrew Entwistle; Emma Frew; Pollyanna Hardy; Kiya Hurley; Laura Jones; et al. (NIHR Journals Library, 2020)
Background: More men than women in the UK are living with overweight or obesity, but men are less likely to engage with weight loss programmes. Healthy Dads, Healthy Kids is an effective Australian weight management programme that targets fathers, who participate with their primary school-aged children. Behavioural interventions do not always transfer between contexts, so an adaptation of the Healthy Dads, Healthy Kids programme to an ethnically diverse UK setting was trialled. Objectives: To adapt and test the Australian Healthy Dads, Healthy Kids programme for delivery to men in an ethnically diverse, socioeconomically disadvantaged UK setting. Design: Phase 1a studied the cultural adaptation of the Healthy Dads, Healthy Kids programme and was informed by qualitative data from fathers and other family members, and a theoretical framework. Phase 1b was an uncontrolled feasibility trial. Phase 2 was a randomised controlled feasibility trial. Setting: Two ethnically diverse, socioeconomically disadvantaged UK cities. Participants: In phase 1a, participants were parents and family members from black and minority ethnic groups and/or socioeconomically deprived localities. In phases 1b and 2, participants were fathers with overweight or obesity and their children aged 4-11 years. Interventions: The adapted Healthy Dads, Healthy Kids intervention comprised nine sessions that targeted diet and physical activity and incorporated joint father-child physical activity. Healthy Dads, Healthy Kids was delivered in two programmes in phase 1b and four programmes in phase 2. Those in the comparator arm in phase 2 received a family voucher to attend a local sports centre. Main outcome measures: The following outcomes were measured: recruitment to the trial, retention, intervention fidelity, attendance, feasibility of trial processes and collection of outcome data. Results: Forty-three fathers participated (intervention group, n = 29) in phase 2 (48% of recruitment target), despite multiple recruitment locations. Fathers' mean body mass index was 30.2 kg/m2 (standard deviation 5.1 kg/m2); 60.2% were from a minority ethnic group, with a high proportion from disadvantaged localities. Twenty-seven (63%) fathers completed follow-up at 3 months. Identifying sites for delivery at a time that was convenient for the families, with appropriately skilled programme facilitators, proved challenging. Four programmes were delivered in leisure centres and community venues. Of the participants who attended the intervention at least once (n = 20), 75% completed the programme (attended five or more sessions). Feedback from participants rated the sessions as 'good' or 'very good' and participants reported behavioural change. Researcher observations of intervention delivery showed that the sessions were delivered with high fidelity. Conclusions: The intervention was well delivered and received, but there were significant challenges in recruiting overweight men, and follow-up rates at 3 and 6 months were low. We do not recommend progression to a definitive trial as it was not feasible to deliver the Healthy Dads, Healthy Kids programme to fathers living with overweight and obesity in ethnically diverse, socioeconomically deprived communities in the UK. More work is needed to explore the optimal ways to engage fathers from ethnically diverse socioeconomically deprived populations in research. Trial registration: Current Controlled Trials ISRCTN16724454. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 8, No. 2. See the NIHR Journals Library website for further project information.